Role of nurses to improve self-care in heart failure patients: a systematic review and meta-analysis. (13th November 2019) - Massimi, A; De Vito, C; Rega, M L; Villari, P; Damiani, G
Abstract: Introduction: Heart Failure (HF) is a pandemic chronic disease with a prevalence up to 3% in the general population, representing the main cause of hospitalization for people over 65. Self-care plays a central role in the management of patients with HF, showing evidence of effectiveness in reducing re-hospitalization rates and mortality. Methods: We carried out a systematic review and meta-analysis to assess the efficacy of nurse-led educational interventions Vs usual care in improving self-care skills of patients with chronic HF. The main biomedical databases were searched for Randomized Control Trials (RCTs) of nurse-led educational interventions performed on adults with a previous diagnosis of HF. Improvement of HF self-management skills (self-care level) was summarized by calculating the standardized mean difference (SMD) and 95% confidence intervals (CI) stratified for the length of the follow-up. Results: Globally, 14 RCTs were included involving 2078 participants. Ten studies showed the efficacy of the interventions at 3 months (short term) with a SMD of 0.78 (95% CI 0.38-1.18) in favor of the self-care education interventions. Five studies reported on self-care abilities at 6-9 months (medium term), not showing statistically significant results (SMD 0.35, 95%CI 0.11-0.81). The long-term effect of the educational interventions showed no statistically significant improvement in self-care behaviors (three studies, SMD 0.05, 95CI% 0.12 - 0.22). Conclusions: These results show that nursing educational interventions improve self-care behaviors in HF, but mainly in the short term. Intensive educational interventions led by nurses, associated with appropriate continuity and transition of care, can determine the best outcomes for patients with HF, strengthening self-care behaviors over time. This approach could have a major impact not only on individual level, but on the general reduction of complications, hospitalization, medical costs and ultimately mortality. Key messages: Nurse-led educational programs have a short-term efficacy in enhancing self-care behaviors among heart failure patients. Post-discharge repeated educational interventions, along with timely and shared plans ruling the transition between the hospital and the other providers, are strongly needed.